Boosting Size‐Selective Hydrogen Combustion in the Presence of Propene Using Controllable Metal Clusters Encapsulated in Zeolite. (29th June 2018) - Shan, Yuling; Sui, Zhijun; Zhu, Yian; Zhou, Jinghong; Zhou, Xinggui; Chen, De
Abstract: A strategy is presented for making metal clusters encapsulated inside microporous solids selectively accessible to reactant molecules by manipulating molecular sieve size and affinity for adsorbed molecules. This expands the catalytic capabilities of these materials to reactions demanding high selectivity and stability. Selective hydrogen combustion was achieved over Pt clusters encapsulated in LTA zeolite (KA, NaA, CaA) in a propene‐rich mixture obtained from propane dehydrogenation, showing pore‐size dependent selectivity and coking rate. Propene tended to adsorb at channels or external surfaces of zeolite, interfering the diffusion of hydrogen and oxygen. Tailoring the surface of LTA zeolite with additional alkali or alkaline earth oxides contributed to narrowing zeolite pore size and their affinity for propene. The thus‐modified Pt@KA catalyst displayed excellent hydrogen combustion selectivity (98.5 %) with high activity and superior anti‐coking and anti‐sintering properties.